Good practice in adult mental health - Ryan, Tony, 1958-; Pritchard, Jacki (Good practice in social work, 2004)
This text is a guide to good practice within adult mental health care, providing a comprehensive introduction to mental health and illness. It is designed to aid mental health professionals and workers, agencies, and any individuals coming in to contact with mental illness, in recognising a mental health need or problem and offering appropriate support. This is an essential introduction written by practitioners, and also draws from the personal experiences of service users and carers, providing up-to-date and topical material covering major issues such as: the concepts of mental health, illnes.